HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN AMENOREA LAKTASI DI RUMAH BERSALIN KASIH IBU - Husna Sari; Erlina Hayati (JURNAL ILMIAH DHDT - KEBIDANAN, 2020)
Mothers who give exclusive breastfeeding and not menstruation, it will not get pregnant for 6 months after gave birth . The purpose of this study was to study whether there is a relationship between exclusive breastfeeding and lactational amenorrhea in the Kasih Ibu Maternity Hospital. This type of research is descriptive research. The population in this study were all mothers who carry 6-12 month babies, both giving and not giving exclusive breastfeeding, to the Kasih Ibu Maternity Hospital. The samples were 80 respondents with accidental sampling technique. Data obtained by collecting questionnaires for respondents and data were analyzed using Chi Square at 95% confidence level. Based on the results of exclusive breastfeeding research with amenorrhoea lactation shows the majority of respondents who provided exclusive breastfeeding were 48 people (60.0%) and those who did not give exclusive breastfeeding for 32 people (40.0%). While mothers who experienced lactation amenorrhoea were 50 people (62.5%) and those who did not amenorrhoea were 30 people (42.5%). Statistical test results p (0,000) <α (0.05) and OR = 47.7, there is a significant relationship between exclusive breastfeeding and lactation amenorrhoea at the Kasih Ibu Maternity Hospital. It is expected that health workers at the Kasih Ibu Maternity Hospital to further enhance counseling and sosialize about importance of exclusive breastfeeding, because there are still many mothers who do not give exclusive breastfeeding and do not know theway and benefits of exclusive breastfeeding as a natural contraceptive device.